2004
DOI: 10.1007/s00595-003-2676-2
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial Cystic Disease of the Femoral Vein: Report of a Case

Abstract: Adventitial cystic disease (ACD) of the veins is a rare phenomenon, and ACD of the femoral vein is particularly difficult to diagnose due to the similarity in symptoms to those of deep vein thrombosis. We report a case of ACD of the femoral vein, which was initially misdiagnosed as deep vein thrombosis, in a 48-year-old woman who presented with a painless swelling in her right lower leg. The extensive cystic involvement of the femoral vein was completely resected and reconstructed with an 8-mm ringed polytetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…[11][12][13][14][15] Axillary and radial artery involvement has also been reported. 16,17 Although CAVD usually presents in the second or fourth decade of life, it is predominantly seen in young healthy individuals with minimal cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 91%
“…[11][12][13][14][15] Axillary and radial artery involvement has also been reported. 16,17 Although CAVD usually presents in the second or fourth decade of life, it is predominantly seen in young healthy individuals with minimal cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 91%
“…There are only 32 reported cases of ACD of the vein in the world literature, including this case. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In contrast, adventitial cystic disease of the artery is a well-described, if rare, cause of intermittent lower extremity arteriogenic claudication occurring in 1:1200 cases of claudication. 19,20 ACD of the artery involves the popliteal artery in 85% of cases.…”
Section: Discussionmentioning
confidence: 94%
“…A more contemporary option is resection of the affected portion of the vein and immediate reconstruction with prosthetic or autologous graft as performed in 5 cases. 8,9,11,12,17 Prosthetic graft was chosen in 4 cases and autologous axillary vein graft in 1 case. Recurrence of a cyst has not yet been reported after vein resection with reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In our patient, the blood flow normalized in the affected vein without the need for reconstruction. The etiology of ACD is unknown, although various authors have suggested "ganglion," "synovial," "embryological," and "mesothelial" theories.…”
Section: Discussionmentioning
confidence: 98%